2014
DOI: 10.2166/wst.2014.284
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary treatment for wastewater reuse based on the Daphnia magna filtration – comparison with conventional tertiary treatments

Abstract: Tertiary treatments are required to permit safe reuse of wastewater. The performance of a new biological tertiary treatment based on the filtration by a population of Daphnia magna was studied and compared with the performance of other conventional tertiary treatments such as coagulation-flocculation, settling tank, disc filtration, sand filtering and ultraviolet (UV) light. The analysis was based on the efficiency in the particle removal and Escherichia coli inactivation. The Daphnia magna treatment reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Schalau et al (2008) found that water temperatures above 6°C guaranteed Daphnia development. Serra et al (2014) found an increase in the Daphnia filtration rate for temperatures above 20°C, which also coincided with a greater food concentration in warmer periods. As mentioned by Burns (1969), in warmer environments Daphnia start to grow earlier than in colder environments (Berger et al 2006).…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…Schalau et al (2008) found that water temperatures above 6°C guaranteed Daphnia development. Serra et al (2014) found an increase in the Daphnia filtration rate for temperatures above 20°C, which also coincided with a greater food concentration in warmer periods. As mentioned by Burns (1969), in warmer environments Daphnia start to grow earlier than in colder environments (Berger et al 2006).…”
Section: Introductionmentioning
confidence: 60%
“…In the experiments of both Serra et al (2014) and Pau et al (2013), Daphnia preyed directly on the suspended sludge particles. Serra et al (2014) did not found any relationship between the removal of E. coli and the particle retention by conventional treatments, in the range of particle sizes from 2.5 to 500 lm. However, they did find that the Daphnia filtration method was more efficient in inactivating E. coli than the conventional particle retention methods, but less efficient than the inactivation attained by UV light.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations